1995
DOI: 10.1046/j.1525-1438.1995.05040282.x
|View full text |Cite
|
Sign up to set email alerts
|

c-erbB-3 proto-oncogene expression in uterine cervical carcinoma

Abstract: Over-expression of epidermal growth factor receptor (EGFR) and c-erbB-2, in uterine cervical carcinomas, is associated with a worsened prognosis. A third member of this proto-oncogene family, c-erbB-3, has now been identified and its over-expression has been described in a variety of carcinomas. In this immunohistochemical study we have shown that c-erbB-3 is widely expressed in cervical carcinomas, but we have found no association between its over-expression and lymph node status or clinical outcome. In a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…gastric cancers (Sanidas et al 1993). cenical cancer (Hunt et al 1995. prostate cancer (Poller et al 1992).…”
mentioning
confidence: 99%
“…gastric cancers (Sanidas et al 1993). cenical cancer (Hunt et al 1995. prostate cancer (Poller et al 1992).…”
mentioning
confidence: 99%
“…The terminal lesion, squamous cell carcinoma, on the other hand, occurred chiefly in women in their sixties. Some authors have suggested that age-related changes, especially mistakes in the apoptotic processes, inheritance of peculiar genes or acquisition of genetic defects could also contribute to the development of morbidities of the cervix [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrable EGFR incervical carcinomas appeared to be associated with a poor prognosis in twostudies(220,221) but was of noprognostic value in another(222). Overexpression ofc‐ erb B‐3 in cervical neoplasms appears to be devoid of any clinicalsignificance(223).…”
Section: Oncogenes and Growth Factorsmentioning
confidence: 98%